A vinyl polymer having pendent sulfones prepared by atom-transfer radical polymerization of a sulfide-containing methacrylate and electrophoretic transparent coating on a stainless-steel anode1. Issue 23 (21st June 2015) - Kameyama, Tomomi; Takasu, Akinori
<x xml:space="preserve">Abstract</x> A vinyl polymer containing pendent sulfones (oxidation > 99%), which was then selectively coated onto a stainless-steel anode by electrophoretic deposition, in which the deposited film was transparent.